A representação social do papel de gestores em organizações não governamentais - Serafim, Lia Sales (2007)
The discussions concerning the absence of a management model appropriate to the peculiarities of third sector organizations have not been impeditive to their emphasized expansion in the last decades. In the attempt of understanding this phenomenon from the perspective of those who manage social organizations, this work based on the theory of social representations to understand the notion that organization managers of the third sector - based in Fortaleza CE - have of the part that they play and how this notion influences the direction of their activities. Social representations of managers of four different categories of non-governmental organizations have been investigated, each category composed of two unities. The categories researched were: social integration through art and education, prevention and treatment of alcohol and drug abuse, children s health assistance and community action. By using Doise s Societal Approach, the role of social managers translated in intraindividual, interindividual and situational processes of their actions, has been analysed within the social representations, focusing on beliefs, values, symbols and stories that give meaning to the existence of non-governmental organizations. Analysis and discussion of data displayed the existence of diversity in the understanding of managers within their practice, in other words, the management profile is also its own manager s. The branch where an organization acts is also preponderant in the shaping of a management style. It could be deduced, from to the organizations researched, that professional formation and the manager s social insertion mainly, are determinative factors in the outlining of a management model of its own. It was concluded that, due to heterogeneity of interests and action segments, there is no systematic process for social management among organizations. Management styles are supported by their director s own perception of achievement, who model organizations according to their contingencies